DEVELOPMENT OF A PANEL OF MONOCLONAL ANTIBODIES FOR STUDYING OF LOCAL PRODUCTION OF CYTOKINES IN CHRONIC RHINOSINUSITIS - E. A. Varyushina; A. V. Zahkov; S. V. Rodin; S. A. Sineva; A. S. Simbirtsev (Инфекция и иммунитет, 2018)
.